Time-based Assessment of Hearing Preservation Rates After Microsurgical Resection of Vestibular Schwannomas: A Systematic Review. Issue 5 (June 2020) - Hunt, Anastasia A.; Cass, Nathan D.; Coughlin, Adam; Gubbels, Samuel P.
Abstract : Objective: To determine short- and intermediate-term hearing preservation rates after microsurgical resection of vestibular schwannoma (VS). Data Sources: Systematic review of the Ovid, Cochrane, EMBASE, and Web of Science databases. Study Selection: This study was restricted to full-text English-language articles detailing VS resection via the middle cranial fossa or retrosigmoid approaches. Documentation of pre- and posttreatment hearing outcomes with American Academy of Otolaryngology–Head and Neck Surgery, Gardner-Robertson, or word recognition score scales, as well as time to follow-up were required. Duplicate data sets, studies with >10% of patients with neurofibromatosis two, previous or nonsurgical VS treatment, case reports with <five patients, or studies detailing decompressive surgery were excluded. Data Extraction: Two authors independently performed full-text reviews to determine study eligibility. Discrepancies were settled by consensus. "Class A/B, I/II" hearing was defined as AAO-HNS Class A or B, Gardner-Robertson Class 1 or 2, or PTA ⩽ 50 dB with word recognition score ≥ 50% on audiogram. Data Synthesis: Pooled estimates of preserved Class A/B, I/II hearing at last postoperative follow-up. Conclusions: Of 1323 reports, 14 were utilized in analyses yielding data from 2, 977 patients. Mean follow-up was 52.5 months (SD = 19.9). Class A/B, 1/2 hearing was preserved at last follow-up in 57% of patients. Meta-regression revealed that resection through the middle cranial fossa was associated with preservation of serviceable hearing. Moreover, when preserved in the immediate postoperative period, it seems to be stable over time. Abstract : Supplemental Digital Content is available in the text